2019
DOI: 10.1002/ajhb.23252
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of adult human bone and skeletal muscle mass to height in the US population

Abstract: Objectives: The scaling of structural components to body size is well studied in mammals, although comparable human observations in a large and diverse sample are lacking. The current study aimed to fill this gap by examining the scaling relationships between total body (TB) and regional bone and skeletal muscle (SM) mass with body size, as defined by stature, in a nationally representative sample of the US population. Methods: Subjects were 17,126 non-Hispanic (NH) white, NH black, and Mexican American men an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 38 publications
(85 reference statements)
3
15
0
Order By: Relevance
“…The geometric models of the head, limbs and trunk were consistent with the results found in Heymsfield et al () and Schuna Jr. et al (). Arms and trunk mass held scaling exponents smaller than leg mass.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The geometric models of the head, limbs and trunk were consistent with the results found in Heymsfield et al () and Schuna Jr. et al (). Arms and trunk mass held scaling exponents smaller than leg mass.…”
Section: Discussionsupporting
confidence: 90%
“…This means that taller individuals increase leg mass at disproportionally higher rates than shorter individuals and taller individuals increase head mass at disproportionally lower rates than shorter individuals. In Heymsfield et al () and Schuna Jr. et al () it was found that arm mass scaled to powers slightly lower than 2.0 and leg mass scaled to powers slightly larger than what we found in this study. We attribute our overestimation to the unrefined simple geometrical models that rely on cylinders for limbs.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations